Neuroimaging as a New Diagnostic Modality in Amyotrophic Lateral Sclerosis - Verstraete, Esther (Neurotherapeutics, 2015)
Amyotrophic lateral sclerosis (ALS) is characterized by progressive degeneration of upper and lower motor neurons, with variable involvement of extramotor brain regions. Currently, there are no established objective markers of upper motor neuron and extramotor involvement in ALS. Here, we review the potential diagnostic value of advanced neuroimaging techniques that are increasingly being used to study the brain in ALS. First, we discuss the role of different imaging modalities in our increasing understanding of ALS pathogenesis, and their potential to contribute to objective upper motor neuron biomarkers for the disease. Second, we discuss the challenges to be overcome and the required phases of diagnostic test development to translate imaging technology to clinical care. We also present examples of multidimensional imaging approaches to achieve high levels of diagnostic accuracy. Last, we address the role of neuroimaging in clinical therapeutic trials. Advanced neuroimaging techniques will continue to develop and offer significant opportunities to facilitate the development of new effective treatments for ALS. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13311-015-0347-9) contains supplementary material, which is available to authorized users.